Construction and Performance Characteristics of Modified Screen Printed and Modified Carbon Paste Sensors for Selective Determination of Cu(II) Ion in Different Polluted Water Samples. Issue 6 (2nd June 2016) - Ali, Tamer Awad; Mohamed, Gehad G.; Said, Amal H.
Abstract : Four new ion-selective electrodes (ISEs), based on N, N ′-bis(salicylaldehyde)- p -phenylene diamine (SPD) as ionophore, are constructed for the determination of copper(II) ion. The modified carbon paste (MCPEs; electrodes I and II) and modified screen-printed sensors (MSPEs; electrodes III and IV) exhibit good potentiometric response for Cu(II) over a wide concentration range of 1.0 × 10 −6 – 1.0 × 10 −2 mol L −1 for electrodes (I and II) and 4.8 × 10 −7 –1.0 × 10 −2 mol L −1 for electrodes (III and IV) with a detection limit of 1.0 × 10 −6 mol L −1 for electrodes (I and II) and 4.8 × 10 −7 mol L −1 for electrodes (III and IV), respectively. The slopes of the calibration graphs are 29.62 ± 0.9 and 30.12 ± 0.7 mV decade −1 for electrode (I) (tricresylphosphate (TCP) plasticizer) and electrode (II) ( o -nitrophenyloctylether o -NPOE plasticizer), respectively. Also, the MSPEs showed good potentiometric slopes of 29.91 ± 0.5 and 30.70 ± 0.3 mV decade −1 for electrode (III) (TCP plasticizer) and electrode (IV) ( o -NPOE plasticizer), respectively. The electrodes showed stable and reproducible potentials over a period of 60, 88, 120, and 145 days at the pH range from 3 to 7 for electrodes (II), (III), and (IV) and pH range from 3 to 6 for electrode (I). This method was successfully applied for potentiometric determination of Cu(II) in tap water, river, and formation water samples in addition to pharmaceutical preparation. The results obtained agree with those obtained with the atomic absorption spectrometry (AAS).